Who wins? Lessons on the use of innovation prizes to achieve social change for the benefit of the very poorest. Issue 1 (2nd January 2022) - Barnett, Christopher Paul; Brown, Cheryl
ABSTRACT: Prize giving has grown exponentially, with agencies like the World Bank and USAID using them to help solve critical development challenges in low-income countries. This paper draws on findings from a DFID programme that has been experimenting with a suite of global prizes, including in Ghana, Kenya, and Nepal. The paper reflects on prizes used to deliver social change: where they work, why, and for whom. We find that development impact can be enhanced when prizes are not implemented alone. Complementary support is often necessary to help innovators participate, overcome barriers, and support innovation that leads to social change.